Sustainable development: divergences and complexities in interpretation - Mazloomi, Mehrdad; Hassan, Ahmad Sanusi (2008)
Unprecedented complexities in confronting economy, society and environment in addition to myriad of systematic dysfunctions resulted in UN sponsored World Commission of Environmental Development (WCED) led by former Norwegian Prime Minister Brundtland in 1987. Its report; Our Common Future; is a well known mile stone in history of eco-friendly thinking since it has a significant effect on sources exploitation, decision making and governance while reinvigorates local and ethnical approaches. Shedding light on future of human and his life on the earth, implications of WCED was legitimating through extensive initiatives taken after 1987 successively. To enhance and develop the WCED achievements, series of them ensued then namely Rio declaration (1992), agenda 21 which followed by local agenda 21 and Habitat (1996). These initiatives were launched to implement diverse facets of sustainability while mostly relied on the definition delivered by Brundtland. Despite of widespread concurrence with that definition, a large number of scholars challenge comprehensiveness of definition and strive to fill its gaps to prevent misleading and ill interpretation. Even several go further and propose definitions based on holism and sophistication. This paper reviews sustainable development concepts and definitions in historical and contemporary context. It discusses on flaws of Brundtland definition and delves into remedial attempts to tackle the issue.